Detection of acute leukaemia cells using variety of features and neural networks - A. S., Abdul Nasir; Mohd Yusoff, Mashor, Prof. Dr.; H., Rosline (Springer-Verlag., 2011)
Link to publisher's homepage at http://springerlink.com/